Applying the Technology Acceptance Model to Design Wellness Tourism E-Guidebook - Putri Luthfiya, Dzulfa; Susanto, Eko; Andrianto, Tomy (Journal of Tourism Sustainability, 2021)
Wellness tourism is becoming one trend as people desire to travel for fitness and mental health purposes. Wellness tourism resources are one of the South Bandung area's advantages. Information media is needed to be an alternative to the market under developing information about wellness tourism in the region. This applied research designed the wellness tourism e-guidebook by applying the Technology Acceptance Model (TAM) as the basis of a design by collecting opinions from 125 respondents who were processed statistically descriptive. The design process uses the canva application, Qr Code, and anyflip. This applied research has resulted in an electronic guidebook created as a reference for information related to wellness tourism in South Bandung. This 66-page book contains four sections in an e-guidebook compiled to meet the practical needs of wellness tourists in South Bandung.